Fritter packaging design to increase the sustainability of micro, small, and medium enterprises - Wirawan, Christina; Sarvia, Elty; Sulandari, Noek; Yapinus, Pin Panji; Tanubrata, Markus; Salim, Gabriel Koesuma; Ismail, Tubagus Panji (JURNAL TEKNIK INDUSTRI, 2024)
Fritter is the traditional food of the people in Indonesia and is very popular and well-liked because of their crunchy, delicious taste, not to mention the affordable price. Fritters are generally sold by street hawkers, a type of business categorized as micro-enterprises. Due to the COVID-19 pandemic, fritter sellers have experienced a drastic drop in sales, because buyers doubt the hygiene of the fritter offered, especially the packaging used. Micro, small, and medium enterprises are the target of the Indonesian government to be supported and empowered. To maintain the sustainability of their business, the efforts that can be made are to design packaging that ensures food hygiene and accommodates customer needs. The design of packaging for the fritter is done based on interviews and the Quality Function Deployment method to accommodate customer needs. The new packaging is designed using thin cardboard covered with kitchen tissue. This packaging improves the function of ordinary packaging, which is more hygienic, absorbs oil and moisture, can be closed tightly, is more durable, and can store leftovers that are not eaten immediately. The packaging is also more eco-friendly because it eliminates the use of plastic bags. Not much research has been done on fritter packaging, so this research is expected to contribute to providing better fritter packaging.